Efficient water management in equine facilities: A solar powered IoT approach for horse stables - Nureisya Dania, Mohd Zuinuddin; Syamimi Mardiah, Shaharum; Muhammad Haniff, Gusrial; Khairunisa, Abdullah; Muhmmad Aqil Hakim, Izudin@Mohamad (Springer, 2024)
The proposed water dispenser system utilizes IoT and solar technology to supply a sustainable and efficient solution for water dispensing. The system utilizes solar power to function as a power source that helps to draw water from the main tank and flow it to the water bucket for the purpose of horse drinking. IoT integrated sensors are coordinated into the system to monitor the water flow and water level in the water bucket as well as send real-time monitoring to a control unit. The control unit controls the level of the water in the bucket as desired. The overall system includes a monitoring system that tracks the water flow and alerts the client or the system administrator through the IoT enabled device in case the water level is abnormal. This guarantees that the water bucket for the horse to drink continuously filled.